Rural Development Strategy Through the Implementation of Desa Sejahtera Mandiri (DSM) - Suprapto, Suprapto (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2025)
Desa Sejahtera Mandiri (DSM) aimed at the public welfare. Efforts is a decrease in the number of poor and provision of skills / soft skills. DSM seeks to finalize the number of poor and welfare efforts in 4 villages (Gajahrejo, Sidodadi, Pamotan, and Lebakjabung). This study would focus on the planning, implementation and program goals DSM. The approach in this study is a participatory policy research. Sources of data in this study is LP2M UM, TKSK, the Village, some recipients of the program, the Youth Village, and Pokdarwis / LMDH. The data collection is done by observation, interviews, focus group discussions (FGD), and documentation study. The results of this study indicate that become effective DSM programs are programs Livable House photo (RTLH), Business Group (KUBE), and the development of tourism. With the program's target beneficiaries in accordance with the criteria according to the data with social welfare problems (POM). Has built 30 RTLH and formed two (2) KUBE per each village. Therefore DSM targets, still two (2) program which takes place from 9 (nine) achievement of the program. In the field of tourism development has aligned travel concept set.